(untitled) (KYAMC Journal, 2017)
Zika virus is a flavivirus related to Dengue virus, yellow fever virus and West Nile virus. It is considered an emerging arbovirus transmitted by mosquito of the genus Aedes. Its first description took place in 1947 in the Zika Forest in Uganda, isolated on Rhesus monkey used as bait to study the yellow fever virus. Clinical picture is characterized as a ’dengue-like’ syndrome, with abrupt onset of fever; and an early onset of evanescent rash, often pruritic. Occasionally the disease has been associated with Guillain-Barré syndrome. The diagnosis can be performed by PCR or by IgG and IgM antibodies detection. No specific treatment or vaccine is available for Zika virus disease. Treatment is generally supportive. Control measures are same for dengue and chikungunya based mostly on health education and vector control. KYAMC Journal Vol. 7, No.-1, Jul 2016, Page 719-725